Пріоритетні напрями інноваційного розвитку - Тебенко, Віта Миколаївна; Завадських, Ганна Миколаївна; Лисак, Оксана Іванівна; Tebenko, Vita; Zavadskykh, Hanna; Lysak, Oksana (Запоріжжя : 2022, 2022)
UA: У статті досліджено основні тенденції сучасного етапу інноваційного розвитку економіки України. Розглянуто зміни у складових інноваційного потенціалу України за останні роки. Встановлено, що протягом цього періоду майже всі складові мали тенденцію до зменшення, а саме – наукова, кадрова та фінансова. Визначено основні чинники, що стримують інноваційний розвиток. Здійснено аналіз інноваційної активності підприємств та фінансового забезпечення інноваційної діяльності. Визначено пріоритетні напрями інноваційної діяльності. Аграрні підприємства продовжують вирішувати багато економічних та соціальних задач шляхом оперативного реагування на зміни що відбуваються. Але низька платоспроможність сільськогосподарських товаровиробників та недостатня інформованість їх щодо новітніх досягнень вітчизняної сільськогосподарської науки стримує оновлення аграрного виробництва новими сортами, технікою, технологіями. EN: The article examines the main trends of the modern stage of innovative development of the agrarian sector of the Ukrainian economy. According to the conclusions of many scientists, the current state of innovative activity in the country, including in the agricultural sector of the economy, is considered unsatisfactory, the reason for this is negative changes in some indicators. The knowledge intensity of the gross domestic product, the level of which is steadily decreasing, was analyzed. According to the given data, the domestic scientific capacity compared to the average indicator for EU countries is five times lower. The question of the development of the scientific sphere of the country in terms of the number of scientific personnel was considered. It was established that the country has a tendency to reduce the number of researchers, which gradually leads to a decrease in scientific potential. It is possible to ensure the country's competitiveness only by creating conditions for anticipatory economic and social development, building an innovation-oriented model of the economy. The domestic agricultural industry has significant land and labor potential, but its effective use is not possible without strengthening and updating the material and technical base, replacing existing technologies with modern ones. Agricultural enterprises continue to solve many economic and social problems by promptly responding to the changes taking place. One of the most important strategic priority directions of the country's innovative activity is "Technological renewal and development of the agro-industrial complex". In this direction, seven medium-term priorities were approved, which are related to the development and implementation of technologies in various sectors of the agro-industrial complex. Among the reasons that have recently inhibited innovative activity in Ukraine is the systematic underfunding of science, which is the source of new discoveries and inventions that eventually transform into innovations. The main problems that occur and hold back the innovative development of the agrarian sector are insufficient financing, a low level of innovative activity of enterprises, a long payback period for innovations, and an insufficient level of stimulation of innovative activity.
Priority directions of innovative development
Тебенко В. М., Завадских Г. М., Лисак О. І. Пріоритетні напрями інноваційного розвитку. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. 2022. Вип. 12. том 3. C. 30-41.
Keywords: модернізація; інновація; інноваційний розвиток; ефективність; технологія; трансфер; інвестиції; наукоємність; modernization; innovation; innovative development; efficiency; technology; transfer; investment; science